Time-activity budgets and behaviour of the Amazilia hummingbird, Amazilia amazilia (Apodiformes: Trochilidae) in an urban environment - Calviño-Cancela, María (Revista de Biología Tropical, 2006)
This study deals with the time-activity budgets of Amazilia amazilia, a territorial hummingbird, and its preferences for different flower species and perches in the gardens of Lima (Peru) in September 2001. A. amazilia spent an important part of its time resting on perches (ca. 80%) and only 15.5% for foraging, devoted essentially to flower visitation and only 0.3% for hunting and drinking water. Territorial defence accounted for 2% of total time, mostly against Coereba flaveola, an introduced nectarivorous species that seem to be an important competitor of A. amazilia. Flower use is not directly related to flower abundance (χ29 = 1 546, p<0.0001), with Justicia brandegeana and red-flowered Salvia splendens being selected and Impatiens balsamina being rejected. The large amount of time spent on the perches makes them an important element of the habitat. The perches selected are typically on trees, close to the flowers visited, and in a low vertical and middle horizontal position, surrounded by low foliage density, probably to minimize heat loss.